UNSUR-UNSUR INTRINSIK PADA NOVEL â€œBUNDA, AKU KEMBALIâ€ KARYA LALU MOHAMMAD ZAENUDIN - Rachmasisca, Frieska Maryova (LPPM STKIP PGRI Bandar Lampung, 2016)
This study was aimed to know and to describe the intrinsic elements of theme, plot, figure/character, setting, point of view, stylistic and message. The method used in this study was descriptive qualitative method. The data was taken from a novel entitled â€œBunda, Aku Kembaliâ€ written by Mohammad Zaenudin, published by Republika, Jakarta 2008, consisted of 296 pages, consisted of 9 parts. The data analysis done in this study was analyzing the parts of novel in the form of sentences or paragraphs shown in the characteristic of the figures.The result of this study shows that the content of Mohammad Zaenudinâ€™s Bunda, Aku Kembali has some morality values. It can be seen from some utterances shown by the acts of the figures. Therefore, based on the result of this study, this novel can be used as a reference in acts in our daily life.